Keynes, Trouton and the Hector Whaling Company. A personal and professional relationship - Basberg, Bjørn L (Business History, 2017)
John Maynard Keynes’ activities on the stock market are well known. One company in which he bought stocks was the Hector Whaling Company Ltd., London – a comparatively small and little known company founded in 1928. The director of this company was Rupert Trouton. He had worked with Keynes for the Government during the First World War, was his student at Cambridge, and became a close partner in the City from the 1920s and onwards. The reason why Keynes invested in Hector was obviously his association with Rupert Trouton. The first part of this paper explores briefly the development of the Hector Whaling Company and its origins in Norway. The main part analyses the relationship between Trouton and Keynes. The focus is on their co-operation relating to Hector Whaling, but their relationship regarding various other businesses, as well as on the personal level, is also described. The paper is based on studies of the Keynes archives in Cambridge as well as newly available archives of the Hector company. The analysis provides new insights to the more general question on the motivations and decisions behind Keynes’ stock market investments as well as the internationalization of the whaling industry in the 1920s and 30s.
Keywords: Sørishavet; hvalfangstindustri; hvalfangstselskaper; hvalindustri; pelagisk; økonomi

"En livbåt halvfull av vann er funnet". Forlis og ulykker i hvalfangsten på 1920-tallet - Børresen, Dag Ingemar (Norsk sjøfartsmuseum. Årbok, 2008)
Keywords: Sørishavet; hvalbåter; hvalfangere; hvalfangstindustri; hvalkokerier; isfangsten; pelagisk; sjøfolk

Dagbok fra en Sydhavstur 1906 - Sørlle, Petter; Kolltveit, Bård (Norsk sjøfartsmuseum. Årbok, 2005)
Keywords: Sørishavet; dagbøker; hvalfangere; hvalfangstindustri; hvalindustri; hvalkokeri; polareksspedisjoner

Productivity in the 20th century Antarctic pelagic shore station whaling: growth and stagnation in two technological regimes. - Basberg, Bjørn L (The Great Circle, 1997)
Keywords: Antarktis; Sørishavet; historie; hvalfangstindustri; hvalfangststasjoner; hvalindustri; pelagisk

Vel blåst! Kommandør Chr. Christensens Hvalfangstmuseum gjennom 75 år 1917-1992 - Wexelsen, Einar (Utkikksposten (Sandefjord) : kontaktorgan for Sandefjordmuseene, 1992)
Keywords: Antarktis; Christen Christensen; Nordmenn; Vestfold; historie; hvalfangere; hvalfangstindustri; pelagisk; polarekspedisjoner

Whaling or Shipping? Conflicts over the Use of the Norwegian Whaling Fleet during World War II - Basberg, Bjørn Lorens (International Journal of Maritime History, 1991)
When the United Kingdom entered World War n in September 1939 the Norwegian merchant marine was immediately affected, as its ships became the targets of German submarines. Between September 1939 and April 1940 (when Norway was occupied by the Nazis), more than fifty Norwegian ships were lost, mainly in the North Sea and the north Atlantic. In November 1939 an agreement was reached between the British government and the Norwegian Shipowners Association to place almost half the Norwegian merchant fleet at Britain's disposal under the so-called "charter parties scheme." The king and the Norwegian government fled to London and established a government-inexile during the German occupation, but before their departure it was decided to establish an agency in the British capital to operate and manage Norwegian shipping. It was named the Norwegian Shipping and Trade Mission (Nortraship) and became the world's largest shipowner, controlling more than one thousand ships at the outset of the war.'
Keywords: Norge; Sørishavet; andre verdenskrig; hvalbåter; hvalfangstindustri; hvalindustri; pelagisk hvalfangst

Ingeniør Sæbjørnsens bukspretter - Ringstad, Jan Erik (Utkikksposten (Sandefjord) : kontaktorgan for Sandefjordmuseene, 1990)
Keywords: Nordmenn; Sørishavet; hvalfangst; hvalfangstindustri; hvalindustri; patenter; pelagisk; utstyr

Zwischen Kooperation und Konfrontation. Deutschland, Norwegen und die Walfangfrage in den 1930er Jahren - Scholl, Lars Ulrich (Sjøfartshistorisk årbok : Norwegian yearbook of maritime history, 1990)
Keywords: Norge; Sørishavet; Tyskland; historie; hvalfangere; hvalfangstindustri; hvalolje; pelagisk; samarbeid

Motortankskipenes inntog. En komparasjon av utviklingen i dansk, norsk og svensk skipsbyggingsindustri, ca. 1912 til 1933 - Basberg, Bjørn L (Sjøfartshistorisk årbok : Norwegian yearbook of maritime history, 1986)
Keywords: Sørishavet; historie; hvalbåter; hvalfangstindustri; pelagisk; skipsbyggerier; skipsfart

Hvorfor gikk det så greitt? Om nedleggelsen av hvalfangstnæringen i Vestfold - Vik, Kjell (Vestfoldminne, 1984)
Keywords: Sørishavet; Vestfold; historie; hvalfangere; hvalfangstindustri; hvalindustri; næring; pelagisk; sjøfolk; økonomi

Hvalbåten gjennom 100 år - Devig, Thor N (Vestfoldminne, 1982)
Keywords: Norge; Sørishavet; Vestfold; båter; hvalfangere; hvalfangstindustri; hvalindustri; lokalhistorie

Bergens deltakelse i den moderne hvalfangst - Tønnessen, Johan Nicolay (Sjøfartshistorisk årbok : Norwegian yearbook of maritime history, 1973)
Keywords: Antarktis; Sørishavet; historie; hvalfangstindustri; hvalfangstselskaper; hvalindustri; skipsfart

"Cutty Shark" i hvalfangsten tjeneste - Berg, Knut (Årbok. Sandefjord bymuseum, 1969)
Keywords: Sørishavet; historie; hvalbåter; hvalfangere; hvalfangstindustri; hvalindustri; pelagisk; skip

"Forlandet" ex "Femern" ex "Foca" - Knap, Johan (Årbok. Sandefjord bymuseum, 1969)
Keywords: Sørishavet; historie; hvalbåter; hvalfangere; hvalfangstindustri; hvalindustri; pelagisk; skip

"Pelagos" ex "Athenic" - Berg, Knut (Vestfold-minne, 1964)
Keywords: Sørishavet; historie; hvalbåter; hvalfangerflåte; hvalfangstindustri; hvalfangstselskaper; hvalindustri; pelagisk

Noen problemer i den moderne hvalfangsts historie - Tønnessen, Johan Nicolay (Vestfold-minne, 1964)
Keywords: Carl Anton Larsen; Henrik Johan Bull; Svend Foyn; Sørishavet; historie; hvalfangstindustri; hvalfangstselskaper; hvalindustri; næring; pelagisk; polareksspedisjoner; økonomi

Tønsbergs sjøfart gjennom 100 år - Eriksen, Erling (Vestfoldminne, 1961)
Keywords: Sørishavet; Vestfold; historie; hvalfangstindustri; hvalkokerier; pelagisk; skipsbyggerier

Til Sydishavet på jakt efter storhvalen - Slaattelid, Aasm. (Hvalfangstliv : spesialorgan for hvalfangst, 1939)
Keywords: Sørishavet; hvalfangere; hvalfangstindustri; hvalindustri; pelagisk; sjøfolk

Ekspansjonen i hvalfangsten. Hvaloljeprisen. - Istre, Henry R (Hvalfangstliv : spesialorgan for hvalfangst, 1937)
Keywords: Antarktis; Lars Christensen; Sørishavet; hvalfangere; hvalfangstindustri; hvalindustri; hvalolje; pelagisk

Modern Norwegian Whaling in the Antarctic - Isachsen, Gunnar (Geographical Review, 1929)
Keywords: Sørishavet; ekspedisjoner; forskning; historie; hvalfangere; hvalfangstindustri; hvalindustri; pelagisk

Den moderne hvalfangstens kausalproblemer - Johnsen, Arne Odd (Historisk tidsskrift)
Keywords: Sørishavet; historie; hvalfangstindustri; hvalindustri; næring; pelagisk; økonomi